THE SUFFERING OF REVEREND EUGEN ŠUTRIN (Review of Croatian History, 2021)
Reverend Eugen Šutrin was a victim of the supremacy of the communist ideological passion that ruled the entire area of Croatia in the immediate post-war period, including the town of Privlaka near Zadar. In this imposed atmosphere, individuals and groups of people who were close to or ideologically committed to the communist principles took it upon them-selves to decide on the fate of others. Quite often, their personal assessments and evaluations resulted in attacks on property and on the lives of individuals for whom they were determined to be their worldview or class enemies. There were two components involved in the case of Rev. Eugen Šutrin, who was murdered at the end of 1945: the first defined him as a worldview opponent and the second saw him as a witness to the events at the Italian concentration camp for civilian internees on Molat. The investigative actions taken against the suspects for the committed crime and the subsequent trials did not fully reveal which of the previously mentioned components was the key motive for the murder of Rev. Eugen Šutrin.